Dengue in Cape Verde: vector control and vaccination - Rodrigues, Helena Sofia (2013)
In 2009, for the rst time in Cape Verde, an outbreak of dengue was reported and over twenty thousand people were infected. Only a few prophylactic measures were taken. The e ects of vector control on disease spreading, such as insecticide (larvicide and adulticide) and mechanical control, as well as an hypothetical vaccine, are estimated through simulations with the Cape Verde data.